Ein kurzer Film über das Lachen . A Short Film About Laughter - Lüthi, Denis D.; Garrido, Nuria Gómez (Hochschule fur Fernsehen & Film Münich, 2007)
Verzio FF Submission Every two weeks, clowns visit an elderly home bringing about laughter and fun. A film about old age from many perspectives.